MANAGEMENT DECISION OPTIONS IN ALLOCATING CROP FARMING HOUSEHOLDS' RESOURCES IN THE DRIER SAVANNAH ZONE OF NIGERIA: A MULTI-OBJECTIVE PROGRAMMING APPROACH - ADEJOBI , A. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The most daunting management task facing the household is the decision on how to efficiently allocate its limited resources among its multiple production goals, which are conflicting. This paper developed an optimal enterprise management option that would ensure efficient utilization of household's scarce resources to meet its production goals of food security, adequate income, and minimum expenditure on labour. Using multistage sampling technique, 400 households were randomly selected and household production and other socio-economic data were analyzed using Goal Programming (GP) model. The GP results revealed that only 4 of the 18 basic cropping activities identified entered the program. The activities and their hectarage allocations in order of importance were Millet/Maize/Rice (1.20 ha). Maize/Guinea corn/cowpea (0.94 ha). Millet/Cowpea (0.16 ha), and Maize/Cowpea/Millet (0.04 ha). An important feature of this management option was that cereal-based mixed cropping had a relatively more significant effect on household needs for food, income, and reduced expenditure on labour than any other activity in the programme. This option would utilize a minimum cost of N6485.2 ha-1 to meet more than 75% of household production goals. Furthermore, land and hired labour were not limited resources. It is recommended that for the goals of food security, increased income, and reduced farm production costs to be achieved by households in the study area, farming households should practice appropriate cereal-based crop enterprise combination.